Nursing care in Alzheimer's disease: an integrative review (Research, Society and Development, 2022)
Alzheimer's disease is the main form of dementia found among the elderly, it is estimated that by 2050 approximately 115 million are carriers of the disease. It starts slowly, and can often take years to be diagnosed, due to the similarity of symptoms associated with other diseases. It is a progressive degenerative pathology with no cure, starting with memory loss, making it impossible to carry out daily activities, with neuropsychiatric and behavioral changes. Nursing care must seek mechanisms to identify the natural symptoms of aging versus the pathological ones and promote interaction between family, patient and caregivers. The aim of the study is to investigate what has been published about nursing care for the elderly with Alzheimer's disease. This is an integrative review research. The search for scientific articles was carried out in the SciELO database, using the terms "Alzheimer's disease" and "nursing care", in all fields, and "nursing" in the area of knowledge. The results obtained in the six articles studied, revealed that nursing has a fundamental role in both prognosis and treatment, in addition, the focus should be on preserving the health of the elderly, their families and caregivers, through guidelines on the progression of the disease, favoring the patient to have a quality care. Nursing care is related to prevention, health promotion and involvement in the family support network, providing security, comfort and living conditions for the family and the elderly. It is concluded that the nurse plays the role of protagonist in the evaluation and elaboration of care, through the nursing consultation. He is also responsible for training his team and promoting health education for all those involved in elderly care.